Pengaruh Work Life Balance, Employee Engagement, Digital Competence, dan Reskilling terhadap Kinerja Karyawan di Dinas XYZ - Rudi Eduar; M Pahlan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study is motivated by the importance of improving employee performance in the digital era, particularly within government institutions that are required to adapt to technological changes and evolving public needs. The objective of this study is to analyze the effects of Work–Life Balance, Digital Competence, Reskilling, and Employee Engagement on employee performance at the XYZ Agency. The research employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to active employees and analyzed using SmartPLS 4.0. The results indicate that all four variables have a positive and significant effect on employee performance, with Work–Life Balance emerging as the dominant factor. These findings confirm that a healthy work–life balance and strong digital competence play a crucial role in enhancing employee performance, while reskilling and employee engagement also contribute positively, albeit with relatively smaller effects.